Поетичне трикнижжя Івана Гнатюка початку 1990-х років: чому Україна не почула пророка «нового літочислення»? - Колошук, Н. (Слово і Час, 2022)
Три поетичні книги початку 1990-х — «Нове літочислення», «Хресна дорога» та «Правда-мста» — включають відновлену ранню лірику й поеми автора-каторжанина. І. Гнатюк увів в українську поезію
теми та проблематику, пов’язані з масовими злочинами сталінської
тиранії, з націоналістичним рухом опору, із загрозами імперської агресії з Москви в час незалежності. Спираючись на класичну поетику в ліриці та великій епічній формі (сонети, балади, цикли, поеми), мистець
створив новий експресивний тип ліричного героя — затятого й безкомпромісного мученика радянської каторги. Тому бездоказові оцінки
Гнатюкової творчості як графоманської спростовуються прикладами
його унікальної майстерності, вільного володіння словом. The poetry books by I. Hnatiuk, edited in independent Ukraine, are especially valuable due
to the first publication of his poems written in prison. He appeared in front of the reader
in his true poetic self, without distortion of censorship, only in the 1990s — in a kind of
poetical trilogy beginning with the collection “New calculus of time” (Kyiv, 1990). Th ree
poetry books from the early 1990s — “New calculus of time”, “Via Dolorosa” and “True
Revenge” — contain the restored early lyrics and poems of the author prisoner. I. Hnatiuk
introduced into Ukrainian poetry the topics and issues related to the crimes of Stalin’s tyranny,
the national resistance movement, and the threats of imperial aggression from Moscow
in the time of Ukrainian independence. Hnatiuk never announced any prophecies of the expected
‘happy future’ in the new Ukraine, although the collections had a distinct prophetic
orientation. The poems of the 1980s and 1990s were also presented, including the cycles
brought to life by the Chornobyl disaster. The poet perceived the man-made environmental
catastrophe as the last ‘wrath of God’, ‘the deadly tornado’ of the atomic Apocalypse. The
evident journalistic component of the three-volume collection requires deeper reading and
study in the context of the post-Soviet literature. Based on the classical poetic means and
great verse epic forms, the poet created a new expressive type of the lyrical character — the
persistent and uncompromising martyr of the Soviet concentration camp. According to the
author of the paper, the unsubstantiated evaluations of Hnatiuk’s works as graphomania can
be easily refuted by examples of his unique mastery and free command of the word.